Endogenous Apelin Is Protective Against Age-Associated Loss of Retinal Ganglion Cells in Mice - Ishimaru, Yuki; Sumino, Akihide; Shibagaki, Fumiya; Yamamuro, Akiko; Yoshioka, Yasuhiro; Maeda, Sadaaki (Frontiers in Aging Neuroscience, 2020)
Age-associated loss of retinal ganglion cells causes visual deficits, but there is not yet any therapeutic agent to prevent the loss of these cells. Herein we report that apelin, an endogenous peptide ligand of APJ receptor, is protective against the age-related loss of retinal ganglion cells in mice. The mRNA expression of apelin was reduced in the retina of old mice compared with that in young mice, whereas retinal APJ expression increased with age. Immunofluorescence staining showed that APJ was present in retinal ganglion cells and their surrounding cells expressed apelin. In addition, both functional and histological analyses demonstrated that apelin deficiency accelerated the loss of retinal ganglion cells associated with age in mice. These results suggest that endogenous apelin plays a protective role against the degeneration of retinal ganglion cells and that the apelinergic axis may be a new target for preventing age-related visual impairment.